Potential Drug Interactions Of Oral Antidiabetic In Prescriptions Of Type 2 Diabetes Mellitus Patients At Kumpulan Pane Hospital - Khairunnisa; Urip Harahap; Rumanda Nurhasanah (International Journal of Science, Technology & Management, 2021)
Diabetes Mellitus is a disease that can cause complications of other diseases so that the treatment to be given becomes more and this has the potential for interactions between drugs that can affect the physiological condition of the patient. The aim of this study is to analyze the potential of oral antidiabetic interactions on prescription at Kumpulan Pane Hospital. Analysis of potential oral antidiabetic interactions on a prescription using quantitative research methods is retrospective descriptive. Prescriptions used are inpatient and outpatient prescriptions for the period January-December 2020 that get oral antidiabetics. Analyze data using Medscape and Drugs.com sites. Based on analysis of 9.818 prescription sheets of diabetes mellitus patients, there were found 6.454 (65.73%) prescription of potential oral antidiabetic interactions. Potential interaction of an oral antidiabetic group of 10.759 (91.45%) drug, the pattern of interaction mechanisms most often is pharmacodynamic 73.25%. The most common type of oral antidiabetic drugs that have potential interactions is the biguanide group (metformin) 36.76%. The severity of the most frequent interactions was 92.21%. The conclusion of the potential interactions oral antidiabetic are still found in prescriptions that is 65.73% at Kumpulan Pane Hospital. Keyword: Potential Drug Interactions, Oral Antidiabetics, Prescription